Motocross biking for competition and for recreation: a prospective analysis of 423 injured riders. Issue 1 (14th October 2015) - Singh, Rohit; Theobald, Peter; Hamad, AK; Hay, Stuart
Abstract : Background: Motocross is a form of motorcycle racing held on established off-road circuits and has been a recreational and competitive sport across the world for over 100 years. In the UK alone, motocross has grown into a phenomenally ambitious and popular franchise. There are over 200 motocross clubs across the country, permitting over 900 events annually. Method: Data were collected prospectively over 4 years (from 2010 to 2014) at our unit. All injuries caused by motocross biking that were referred to our trauma and orthopaedic department were included in this study, regardless of whether the rider was performing the sport competitively or recreationally. Results: During the period studied (4 years), 423 patients were included with a total of 485 injuries, ranging from 1 to 6 injuries per patient. The patient's age range was from 4 to 73 years, with most of the injuries being sustained within the early spring and summer months representing the start of the motocross season. Conclusions: We present the first epidemiological study of motocross injuries in the UK. Within the growing culture of 'adrenaline sports', motocross has become an exhilarating and extremely fashionable pastime. This study has identified and categorised the spectrum of injuries from upper limb fracture dislocations to life-threatening head and chest injuries, some of which are serious and may cause significant morbidity and possible mortality. These injuries could have significant resource implications, especially for smaller rural hospitals.